RESISTING THE OTHER: WOMEN’S EXISTENTIALISM AGAINST PATRIARCHAL CULTURE IN SELECTED DISNEY PRINCESS SONG LYRICS - Muhajir, Fatimah; Tantri, Agra Liz; Yetty, Yetty (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
This study, “Resisting the Other: Women’s Existentialism Against Patriarchal Culture in Selected Disney Princess Soundtrack Lyrics”, examines existentialist feminist themes in three Disney Princess songs: “Reflection” (Mulan), “Speechless” (Aladdin), and “Touch the Sky” (Brave). Using Simone de Beauvoir’s concept of “the Other” in Feminist Existentialism, the research analyzes how the lyrics reflect women’s struggles against patriarchal culture by asserting identity, autonomy, and freedom. The findings reveal distinct forms of resistance in each song. “Reflection” portrays women’s rejection of objectification and their demand for self-definition against restrictive gender roles. “Speechless” emphasizes an outright refusal of patriarchal silencing, expressing determination to voice resistance and claim agency. “Touch the Sky” highlights the pursuit of individual liberty, underscoring women’s ability to transcend imposed roles and choose their own paths. Collectively, these songs construct narratives of empowerment that resist the relegation of women to “the Other.” They affirm existential freedom and authenticity as essential to women’s self-realization, illustrating how popular culture can serve as a medium of resistance. By foregrounding women’s voices, Disney Princess soundtracks not only reflect evolving portrayals of women but also contribute to wider discourses on gender equality and female agency in contemporary society.